Proceedings of the Abstracts of Jaffna University International Research Conference (JUICE-2012) Kinship Terms in Jaffna Tamil Dialect: A Sociolinguistic Study - Sivarani, S. (JUICE- 2012 University of Jaffna, 2012)
The main objective of this paper is to classify the kinship terms used in modern Jaffna Tamil social structures and life styles which were collected through field work. This classification is basically undertaken by differentiating and identifying the semantic contents of the collected kinship terms. Further more detail descriptive analysis is done on the usage of the kinship terms in different social contexts, based on the information collected from field work reports. Sociolinguists analyse the relationships between language and society by studying the structure of the kin relation kinship terms. A common methodology is used in sociolinguistics analysis is a descriptive analysis based on field work. This study also involves the descriptive type of methodology. Appropriately, wherever possible and necessary, historical explanation of the form use and semantics of kinship terms are given in this paper. Descriptions of historical explanations are generally based on Tamil literatures and dictionaries. Out of 132 kinship terms collected through field work, we found out only 38 are identified to be common to lexicon, kriya and Jaffna spoken variety. Detail analysis was done to understand the functions of the kinship terms in Jaffna society. We investigated how kinship terms are used in the various social environments, viz. terms of address and references, non kinsfolk, fictive kinship usage, personal names and divine relationships. The work and analysis undertaken in this paper significantly contributes to identify the social pattern of the Jaffna society, via the kin relationship between the society and the language. In addition to this, the work provides useful information to understand more on the descriptive, historical and comparative views of the Jaffna Society.
Keywords: Kinship; Jaffna Tamil Dialogue; Sociolinguistics; emantics